Saturation Transfer Difference NMR Studies of the Interaction of the Proteinkinase CK2 with Peptides - Rauber, Christoph; Berger, Stefan (Protein and Peptide Letters, 2012)
Saturation Transfer Difference NMR (STD NMR) is used for the detection of the binding constant of the decapeptide RRRDDDSDDD with CK2α, the catalytic subunit of the proteinkinase CK2. For this work a valid irradiation frequency of the CK2α had to be found ensuring that no peptide resonance is affected by the irradiation. This is the principle problem for investigations of protein peptide interactions by STD NMR due to the similarity of protein and peptide resonances. It is shown that by careful selection of the irradiation point a KD value averaging to 1 mM can be found. In addition, preferred binding sites of the peptide are detected and it is shown that the side chains of serine and aspartate are closest to the protein surface.
Keywords: proteinkinase CK2